2009
DOI: 10.1152/ajpendo.00014.2009
|View full text |Cite
|
Sign up to set email alerts
|

Hypocaloric high-protein diet improves fatty liver and hypertriglyceridemia in sucrose-fed obese rats via two pathways

Abstract: The mechanism by which replacement of some dietary carbohydrates with protein during weight loss favors lipid metabolism remains obscure. In this study, we investigated the effect of an energy-restricted, high-protein/low-carbohydrate diet on lipid metabolism in obese rats. High-sucrose-induced obese rats were assigned randomly to one of two energy-restricted dietary interventions: a carbohydrate-based control diet (CD) or a high-protein diet (HPD). Lean rats of the same age were assigned as normal control. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 37 publications
4
41
2
Order By: Relevance
“…Recently, it has been shown that glucagon modulates Fgf-21 expression [12][13][14][15]. Here, we extend these observations by reporting for the first time that glucagon increases, independently of endogenous insulin levels, circulating levels of FGF-21 in humans and rodents.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Recently, it has been shown that glucagon modulates Fgf-21 expression [12][13][14][15]. Here, we extend these observations by reporting for the first time that glucagon increases, independently of endogenous insulin levels, circulating levels of FGF-21 in humans and rodents.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, removal of exogenous insulin in humans with type 1 diabetes resulted in an approximately 10% increase in plasma FGF-21 [18], suggesting that insulin reduces FGF-21. In addition, insulin inhibited glucagonstimulated Fgf-21 expression in rat hepatocytes [12].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations